Early Ground‐Based Work by Auroral Pioneer Carl Størmer on the High‐Altitude Detached Subauroral Arcs Now Known as "STEVE". Issue 3 (28th February 2020) - Hunnekuhl, Michael; MacDonald, Elizabeth
Abstract: STEVE (Strong Thermal Emission Velocity Enhancement) phenomenon related structures have received much attention from space weather audiences in recent years. MacDonald et al. (2018, https://doi.org/10.1126/sciadv.aaq0030 ), reports on a link between these ionospheric structures and the subauroral ion drift for the first time. This commentary summarizes previously overlooked observations of a distinct type of detached subauroral arc by the aurora pioneer Carl Størmer in Norway between 1911 and 1940, including coordinated simultaneous multistation‐based altitude measurements. This commentary points out that his phenomenological descriptions and height measurements show a striking resemblance to modern descriptions and measurements of STEVE. Plain Language Summary: Discussions by the amateur aurora observer community with the citizen science project Aurorasaurus and the scientific community initiated the discovery of the significance of seemingly new aurora or aurora‐like structures. They occur detached, toward the equator, from the auroral ovals. They are linked to atypically high ion temperatures and velocities in the subauroral ion drift, a narrow ionospheric structure with an extended east‐west structure. MacDonald et al. (2018) describe these structures for the first time in the modern literature and have introduced the term STEVE (Strong Thermal Emission Velocity Enhancement) for the phenomenon. Little known today are the early observations and measurements of the aurora pioneer Carl Størmer on a distinct type of aurora‐like arc observed detached, toward the equator, from the main zone of aurora activity, and mostly published in lesser known journals in the 1930s and 1940s. Størmer and his team were able to determine the unusually high heights of these structures. This commentary shows that his descriptions and height measurements show a striking resemblance to modern descriptions of STEVE. Størmer's work is an example that shows these early publications can still contribute to topics of high interest in the space weather field today. Key Points: Carl Størmer reported on observations of subauroral arcs, interpreted as STEVE arcs, for seven individual days between 1911 and 1940 Carl Størmer reported on height measurements for subauroral arcs, interpreted as STEVE arcs, ranging from 138 to 259 km Størmer's and earlier descriptions of subauroral arcs by Bond et al. (1889), interpreted as STEVE arcs, indicate unusual spectra